Neurons gating behavior—developmental, molecular and functional features of neurons in the Substantia Nigra pars reticulata - Partanen, Juha; Achim, Kaia (Frontiers in Neuroscience, 2022)
The Substantia Nigra pars reticulata (SNpr) is the major information output site of the basal ganglia network and instrumental for the activation and adjustment of movement, regulation of the behavioral state and response to reward. Due to both overlapping and unique input and output connections, the SNpr might also have signal integration capacity and contribute to action selection. How the SNpr regulates these multiple functions remains incompletely understood. The SNpr is located in the ventral midbrain and is composed primarily of inhibitory GABAergic projection neurons that are heterogeneous in their properties. In addition, the SNpr contains smaller populations of other neurons, including glutamatergic neurons. Here, we discuss regionalization of the SNpr, in particular the division of the SNpr neurons to anterior (aSNpr) and posterior (pSNpr) subtypes, which display differences in many of their features. We hypothesize that unique developmental and molecular characteristics of the SNpr neuron subtypes correlate with both region-specific connections and notable functional specializations of the SNpr. Variation in both the genetic control of the SNpr neuron development as well as signals regulating cell migration and axon guidance may contribute to the functional diversity of the SNpr neurons. Therefore, insights into the various aspects of differentiation of the SNpr neurons can increase our understanding of fundamental brain functions and their defects in neurological and psychiatric disorders, including movement and mood disorders, as well as epilepsy.